2020
DOI: 10.1002/iub.2296
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 gene editing: A new therapeutic approach in the treatment of infection and autoimmunity

Abstract: CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/ CRISPR-associated protein9) may be viewed as an adaptive bacterial immune system. When a virus infects a bacterium, a fragment of the virus genome is inserted into the CRISPR sequence of the bacterial genome as a memory.When the bacterium becomes infected again with the same virus, an RNA molecule that is a transcript of the memory sequence, directs Cas9, an endonuclease, to the complementary region of the virus genome, and Cas9 disables t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 142 publications
0
21
0
2
Order By: Relevance
“…In fact, a combination of innate immunity, antibody production, and cytotoxic function of TCD8 + cells is involved in anti-viral defense in the respiratory tract, and effector CD4 + T cells play an indirect but important role in anti-viral defense by leading these events. In HIV infection, where T CD4 + cells are targeted as the main target, the immune system is significantly weakened, indicating the high importance of these cells in the immune system [ 25 ]. Figure 1 summarizes the above-mentioned events.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, a combination of innate immunity, antibody production, and cytotoxic function of TCD8 + cells is involved in anti-viral defense in the respiratory tract, and effector CD4 + T cells play an indirect but important role in anti-viral defense by leading these events. In HIV infection, where T CD4 + cells are targeted as the main target, the immune system is significantly weakened, indicating the high importance of these cells in the immune system [ 25 ]. Figure 1 summarizes the above-mentioned events.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, researchers suggest that the regulatory functions of circular RNAs and targeting the mammalian target of rapamycin signaling are effective in cancer therapy [23,24]. Also, much evidence supports the CRISPR/Cas9 technology and it can be used to better understand the pathogenesis of diseases [25]. The relative abundance of seven IgG glycans, fucose, sialic acid, galactose, and bisecting change during tumor growth in CRC [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the treatment of monogenic diseases, CRISPR-Cas systems have been utilized to treat infectious diseases, such as viral infections (human immunodeficiency virus infection, hepatitis virus infections, and oncogenic virus infections), nonviral infections (bacterial, fungal, and parasite infections), and the potential efficacy has been observed in a number of occasions. 56 Acquired immunodeficiency syndrome (AIDS) caused by infection of human immunodeficiency virus (HIV) is still one of the world's most serious public health challenges. 57 Yin et al reported that the CRISPR-Cas9 tool could inhibit multiple steps of HIV-1 infection, 58 and several research labs have made excellent efforts to improve the use of CRISPR-Cas9 for treating HIV infection.…”
Section: Preclinical Testsmentioning
confidence: 99%